An Exploration of Calligraphic Art within the Context of Islamic Thought - Mauliska, Nur (Universitas Islam Zainul Hasan Genggong, 2025)
This research discusses and describes the importance of calligraphy art in the view of Islam. In Islam, art is seen as something very valuable, and encourages appreciation of beauty, science, technology, and art itself. Calligraphy, as one of the art forms that plays an important role in Islam, is a written art that has high aesthetic value. According to Shaykh Shamsuddin al-Afkani, calligraphy includes understanding the shape of letters, the placement of letters, and how to assemble them into quality writing. Calligraphy reflects the deep meaning of art in Islam and becomes a distinctive spiritual expression. This research uses the literature study method by collecting data from various sources such as books and scientific reports that are relevant to the topic of study. The findings show that the art of calligraphy in Islam has a unique and distinctive aesthetic beauty, and is part of the Arab cultural heritage that needs to be appreciated and understood wholeheartedly.